Verification of Liquefaction Potential during the Strong Earthquake at the Border of Thailand-Myanmar - Mase, Lindung Zalbuin; Likitlersuang, Suched; Tobita, Tetsuo (Journal of earthquake engineering : JEE, 2022)
The study presents a liquefaction potential analysis for the Thailand-Myanmar border area due to the earthquake. Three sites reported liquefaction during Tarlay earthquake in 2011 were investigated including a microtremor to obtain the shear wave velocity profile and depth of engineering bedrock. Next-generation attenuation model was used to estimate the peak ground acceleration at the liquefied sites. A seismic ground response analysis was then conducted, and the result revealed that the shallow sand layers were very vulnerable to undergo liquefaction. The results also showed a similar tendency to the predictions based on the empirical methods.